Teaching English Through UbD: Challenges of Indonesian Pre-Service Teachers - I Ketut Wardana (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2024)
Understanding by Design (UbD) can guide pre-service teachers (PST) in creating intended learning outcomes. However, there is still limited research focusing on the mechanisms of UbD. Therefore, this study aimed to assess UbD’s impact on pre-service teachers’ teaching and assessment skills and the challenges they face. one group-pre-test post-test design within a quasi experiment was conducted to examine the ongoing process of UbD implementation in a real classroom setting. The investigation involved 17 PSTs from the Faculty of Teacher Training and Education in Denpasar for 7 weeks. The instruments included a teaching performance rubric, an observation checklist, and reflective journals. The data were analyzed using descriptive statistics, paired sample t-tests, and thematic analysis. The results indicated that PSTs’ teaching skills significantly improved with Understanding by Design (UbD), as evidenced by an increase in the average score from 70.74 in Cycle 1 to 81.91 in Cycle 2, with more students achieving higher performance ratings after receiving feedback and reinforcement. Referring to T-test outputs p=0.000 > α=0.05 This study concludes that UbD significantly impacts PST’s teaching skills however, challenges remain in connecting cognitive-behavioral skills to real-world applications. Future research should explore specific strategies to address these challenges and investigate UbD’s long-term effects on teaching precision and student engagement.